OPTIMASI PENUGASAN WILAYAH KERJA FIELD ASSISTANT MENGGUNAKAN ASSIGNMENT MODEL GUNA MEMINIMALKAN WAKTU PERJALANAN OPERASIONAL - Elfhian Hutasoit; Jhon Kristopel Manalu; Parapat Gultom (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The efficiency of field personnel mobility is a determining factor in a company's operational success, particularly for the Field Assistant profession, who is responsible for supervision, inspection, and coordination across various work sector areas. Non-optimal territorial assignment often results in wasted travel time, increased operational costs, and personnel fatigue. This study aims to determine the optimal assignment combination of four Field Assistants to four strategic work areas of PT Prima Karya Berjaya in North Sumatra by minimizing total daily travel time. An operational quantitative approach was applied through the Assignment Model using the Hungarian Algorithm with the assistance of QM for Windows version 5 software. Travel time data were obtained from recording the average daily actual travel duration using GPS-based navigation during the observation period. The analysis results show that the model successfully identified the optimal allocation, reducing total field travel time from 275 minutes to 200 minutes per operational inspection cycle, equivalent to a 27.2% duration reduction. These findings prove that a computational-based operations research approach can significantly enhance actual working time productivity in the field. The managerial implication of this study recommends implementing the assignment model as a periodic scheduling instrument to maintain the efficiency of human resource asset movement in the field.